Susceptibility of rat non-alcoholic fatty liver to the acute toxic effect of acetaminophen - Kučera, Otto; Roušar, Tomáš; Staňková, Pavla; Haňáčková, Lenka; Lotková, Halka; Podhola, Miroslav; Cervinková, Zuzana (Journal of gastroenterology and hepatology, 2012)
BACKGROUND AND AIM: Acetaminophen overdose is the most frequent cause of acute liver failure. Non-alcoholic fatty liver disease is the most common chronic condition of the liver. The aim was to assess whether non-alcoholic steatosis sensitizes rat liver to acute toxic effect of acetaminophen. METHODS: Male Sprague-Dawley rats were fed a standard diet (ST-1, 10% kcal fat) and high-fat gelled diet (HFGD, 71% kcal fat) for 6 weeks and then acetaminophen was applied in a single dose (1 g/kg body weight). Animals were killed 24, 48 and 72 h after acetaminophen administration. Serum biochemistry, activities of mitochondrial complexes, hepatic malondialdehyde, reduced and oxidized glutathione, triacylglycerol and cholesterol contents, and concentrations of serum and liver cytokines (TNF-α, TGF-β1) were measured and histopathological samples were prepared. RESULTS: The degree of liver inflammation and hepatocellular necrosis were significantly higher in HFGD fed animals after acetaminophen administration. Serum markers of liver injury were elevated only in acetaminophen treated HFGD fed animals. Concentration of hepatic reduced glutathione and ratio of reduced/oxidized glutathione were decreased in both ST-1 and HFGD groups at 24 h after acetaminophen application. Mild oxidative stress induced by acetaminophen was confirmed by measurement of malondialdehyde. Liver content of TNF-α was not significantly altered, but hepatic TGF-β1 was elevated in acetaminophen treated HFGD rats. We did not observe acetaminophen-induced changes in activities of respiratory complexes I, II, and IV and activity of caspase-3. CONCLUSION: Liver from rats fed HFGD is more susceptible to acute toxic effect of acetaminophen, compared to non-steatotic liver.
Keywords: Acetaminophen; Fatty Liver; játra; Cholesterol; Triglycerides; lékové postižení jater; Malondialdehyde; cholesterol; glutathiondisulfid; Non-alcoholic Fatty Liver Disease; Risk Factors; paracetamol; nekróza; transformující růstový faktor beta1; rizikové faktory; Time Factors; krysa rodu Rattus; Biomarkers; Transforming Growth Factor beta1; zvířata; Electron Transport Chain Complex Proteins; kaspasa 3; Glutathione; časové faktory; náchylnost k nemoci; Disease Susceptibility; ztučnělá játra; TNF-alfa; triglyceridy; potkani Sprague-Dawley; biologické markery; Liver; Caspase 3; stupeň závažnosti nemoci; Male; Chemical and Drug Induced Liver Injury; elektronový transportní řetězec; nealkoholová steatóza jater; glutathion; Severity of Illness Index; Rats; Tumor Necrosis Factor-alpha; Rats, Sprague-Dawley; Animals; mužské pohlaví; Necrosis; Disease Models, Animal; malondialdehyd; Glutathione Disulfide; modely nemocí na zvířatech